2017
DOI: 10.1002/jcb.26122
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Induces Cell Cycle Arrest and Apoptosis of Chondrosarcoma by Targeting TCF‐1/SOX9 Axis

Abstract: Chondrosarcoma is the second most malignant bone tumor with poor prognosis and limited treatment options. Thus, development of more effective treatments has become urgent. Recently, natural compounds derived from medicinal plants have emerged as promising therapeutic options via targeting multiple key cellular molecules. Andrographolide (Andro) is such a compound, which has previously been shown to induce cell cycle arrest and apoptosis in several human cancers. However, the molecular mechanism through which A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…At the end of various treatments, Saos‐2 and U2 OS cells were harvested by trypsinization, and were washed twice with ice‐cold PBS. The apoptotic cells were determined by flow cytometry using Annexin V‐APC/7‐amino‐actinomycin D (7‐AAD) Apoptosis Detection Kit (KeyGEN Biotechnology, Nanjing, China) . The results were analyzed by FlowJo 7.6.5 software (FlowJo Enterprise, Ashland, KY).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of various treatments, Saos‐2 and U2 OS cells were harvested by trypsinization, and were washed twice with ice‐cold PBS. The apoptotic cells were determined by flow cytometry using Annexin V‐APC/7‐amino‐actinomycin D (7‐AAD) Apoptosis Detection Kit (KeyGEN Biotechnology, Nanjing, China) . The results were analyzed by FlowJo 7.6.5 software (FlowJo Enterprise, Ashland, KY).…”
Section: Methodsmentioning
confidence: 99%
“…The apoptotic cells were determined by flow cytometry using Annexin V-APC/7-amino-actinomycin D (7-AAD) Apoptosis Detection Kit (KeyGEN Biotechnology, Nanjing, China). 20 The results were analyzed by FlowJo 7.6.5 software (FlowJo Enterprise, Ashland, KY).…”
Section: Cell Apoptosis Analysis By Flow Cytometrymentioning
confidence: 99%
“…It has been proved that Andro possess various biological activities such as anti-inflammation, anti-infection, immune system regulation, anti-cardiovascular disease, and anticancer effects (13)(14)(15). Previous studies have shown that Andro exhibited potential antitumor activity in various malignancies, including gastric cancer (16), chondrosarcoma (17) and colorectal cancer (18). However, whether Andro suppresses the growth of human melanoma cells and its potential molecular mechanisms were still not well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of curative surgery with chemotherapy has improved the five-year of patients with chondrosarcoma, but many of these patients either do not respond to chemotherapy or develop drug resistance to current chemotherapy regimens [39]. Therefore, the discovery of effective anticancer activities with few side effect chemotherapeutic agents is necessary and urgent.…”
Section: Discussionmentioning
confidence: 99%